Obstetrician-Gynecologists and Perinatal Infections: A Review of Studies of the Collaborative Ambulatory Research Network (2005-2009) - Meaghan A. Leddy; Bernard Gonik; Jay Schulkin (Hindawi Limited, 2010)
Background. Maternal infection is associated with adverse pregnancy outcomes, and ob-gyns are in a unique position to help prevent and treat infections. Methods. This paper summarizes studies completed by the Research Department of the American College of Obstetricians and Gynecologists regarding perinatal infections that were published between 2005 and 2009. Results. Obstetrician-gynecologists are routinely screening for hepatitis B and HIV, and many counsel prenatal patients regarding hepatitis B and toxoplasmosis. However, other infections are not regularly discussed, and many cited time constraints as a barrier to counseling. A majority discusses the transmission of giardiasis and toxoplasmosis, but few knew the source of cryptosporidiosis or cyclosporiasis. Conclusions. Many of the responding ob-gyns were unaware of or not adhering to infection management guidelines. Obstetrician-gynecologists are knowledgeable regarding perinatal infections; however, guidelines must be better disseminated perhaps via a single infection management summary. This paper identified knowledge gaps and areas in which practice can be improved and importantly highlights the need for a comprehensive set of management guidelines for a host of infections, so that physicians can have an easy resource when encountering perinatal infections.